P702 Off-label drug use in patients with inflammatory bowel disease: a national survey among tertiary care centres. (25th January 2019) - Simsek, M; Hoentjen, F; Oldenburg, B; Ponsioen, C Y; van der Woude, J; van der Meulen, A E; Pierik, M; Dijkstra, G; de Boer, N K
Abstract: Background: In daily clinical practice, drugs are commonly prescribed outside the terms of product license, also known as off-label prescribing. Off-label drugs create alternative treatment options, but are associated with unknown safety risks since they are under-evaluated for unlicensed indications. The use of off-label drugs for the treatment of inflammatory bowel diseases (IBD) has not been characterised. We aimed to assess the proportion and characteristics of off-label prescribing for IBD in tertiary care in the Netherlands. Methods: A prospective database of IBD patients from all university hospitals in The Netherlands was used to collect data on (historical) drug prescriptions for IBD and demographics. Drugs were classified as off-label if they were unlicensed for Crohn's disease and/or ulcerative colitis. Uni- and multi-variate analyses were used to identify patient-specific characteristics predictive of increased off-label use. Results: A total of 12 651 historical and current drug records for the induction and/or maintenance treatment of 4583 IBD patients (59% female and 62% Crohn's disease) were available in the database. Of these, 2374 (19%) were considered off-label drug prescriptions. Out of 4583 IBD patients, 1477 (32%) were exposed to off-label drugs. Commonly prescribed off-label IBD drugs were mercaptopurine (18%), beclomethasone (12%), thioguanine (4%) and allopurinol (3%). Off-label prescriptions were more common in ulcerative colitis than Crohn's disease (37% vs. 29%, p < 0.001). Smokers and patients exposed to multiple ( ≥5) types of drugs during their disease course were more likely to be exposed to off-label drugs (smoking 33% vs. 27% and multiple (≥5) drug use 66% vs. 22%, both p < 0.001). Conclusions: About 19% of prescriptions for IBD were off-label and one-third of IBD patients, especially patients with ulcerative colitis, were exposed to off-label drugs. Future studies are needed to evaluate the consequences of off-label prescriptions for the treatment of IBD.